Dry‐Type Artificial Muscles Based on Pendent Sulfonated Chitosan and Functionalized Graphene Oxide for Greatly Enhanced Ionic Interactions and Mechanical Stiffness. (28th June 2013) - Jeon, Jin‐Han; Cheedarala, Ravi Kumar; Kee, Chang‐Doo; Oh, Il‐Kwon
Abstract Biopolymer‐based artificial muscles are promising candidates for biomedical applications and smart electronic textiles due to their multifaceted advantages like natural abundance, eco‐friendliness, cost‐effectiveness, easy chemical modification and high electical reactivity. However, the biopolymer‐based actuators are showing relatively low actuation performance compared with synthetic electroactive polymers because of inadequate mechanical stiffness, low ionic conductivity and ionic exchange capacity (IEC), and poor durability over long‐term activation. This paper reports a high‐performance electro‐active nano‐biopolymer based on pendent sulfonated chitosan (PSC) and functionalized graphene oxide (GO), exhibiting strong electro‐chemo‐mechanical interations with ionic liquid (IL) in open air environment. The proposed GO‐PSC‐IL nano‐biopolymer membrane shows an icnreased tensile strength and ionic exchange capacity of up to 44.8% and 83.1%, respectively, and increased ionic conductivity of over 18 times, resulting in two times larger bending actuation than the pure chitosan actuator under electrical input signals. Eventually, the GO‐PSC‐IL actuators could show robust and high‐performance actuation even at the very low applied voltages that are required in realistic applications.